CLINICAL CHARACTERISTICS AND FACTORS ASSOCIATED WITH METASTASIS AMONG BREAST CANCER PATIENTS AT CA MAU GENERAL HOSPITAL FROM 2022 TO 2024 (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of metastasis and analyze factors associated with metastatic status among breast cancer patients treated at Ca Mau General Hospital from 2022 to 2024.Subjects and Methods: A retrospective cross-sectional study was conducted on 579 histologically confirmed breast cancer patients with immunohistochemistry results. Metastatic status was analyzed using logistic regression.Results: The prevalence of metastasis was 21.76%. The most common metastatic sites were lung (34.13%), bone (33.33%), and liver (29.37%). Multivariable analysis showed that triple-negative subtype (aOR = 4.08; 95%CI: 2.12-7.86), HER2-enriched subtype (aOR = 2.21; 95%CI: 1.18-4.13), histological grade 3 (aOR = 3.97; 95%CI: 1.74-9.05), grade 2 (aOR = 2.41; 95%CI: 1.09-5.31), longer disease duration (trend aOR = 1.89; 95%CI: 1.22-2.93), and right-sided breast cancer (aOR = 1.41; 95%CI: 1.01-2.12) were associated with metastatic status.Conclusion: The prevalence of metastasis among breast cancer patients in this study was 21.76%. Molecular subtype, histological grade, and disease duration were factors associated with metastatic status. Comprehensive assessment of histopathological and molecular characteristics is important for guiding monitoring and management of breast cancer patients.
Keywords: breast cancer, metastasis, IHC subtype, histological grade.